Lens of the present pasts reimagining a histo-cultural trail for Tondo, Manila, through a hybridized landscape-based walking approach - Trias, Edrianne Rae M.
Tondo has been home to many of the country's artists, revolutionaries, organizations, and heritage sites. Despite its rich histo-cultural past, it is challenged by negative stereotypes attached to its place character, such as poverty and violence, as proven by the study’s evidence synthesis procedure and landscape perception survey. This challenge is aggravated by the lack of community awareness and involvement despite the beautification attempts. The thesis aimed to reimagine and reinterpret the spaces of Tondo using the users' perceptions and online experiences of the past and present state of the place to propose a histo-cultural trail that highlights relevant local narratives and identities. A critical component of the study was the development of online tools that the participants used to explore the site despite the pandemic - the CyberWalk Tool Kit. The kit included (a) an online interactive map of Tondo, featuring descriptions, Past PDFs, 360° tours, reframed videos, and site images; and (b) a post-questionnaire about the participants' experience and memory of the CyberWalk. These hybridized tools were used to analyze the community’s intangible histo-cultural perceptions and interpretations. The results found that non-residents had a more negatively-inclined perception of Tondo than locals. However, many locals were also unaware of the histocultural aspects of their spaces. It also established which areas and histo-cultural elements of the polity were included and translated into a trail. Overall, the CyberWalk Tool Kit was assessed to be effective in reimagining spaces histo-culturally and ensuring a significance-led conservation proposal by involving the community in the process. However, its accessibility and development could be further improved to aid future landscape researchers more efficiently.